Promises to keep : the oath in biblical narrative - Ziegler, Yael. (Vetus Testamentum, Supplements, 2008)
While many studies explore the literary role of the oath in general literature, none have contended with the role of the oath in the biblical narratives. This study seeks to fill that vacuum. The first section of this study examines the literary significance of the various oath formulae that appear in biblical narratives, focusing on anomalous formulations of the respective oath formulae. The second section of this study explores the narratives surrounding two characters, Saul and David, both of whom frequently engage in oath-making. The oaths taken by, to and about these characters mirror the narrative itself, and function as a prism through which the character's career is refracted. This study demonstrates that by perceiving the oath as a literary device for plot and character development, additional or more precise meanings may be revealed in the biblical stories.